The Strategic Analysis of Digital Solutions Implementation in the Urban Governance - O. V. Dmitrieva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The article aimed to conduct strategic analysis of digital solutions implementation in the urban governance. For that purpose international practice of digital transformation of such cities as Singapore, Shanghai, Hong Kong, London and Barcelona was discussed and the best practices of digital solutions implementation in Moscow and other Russian regions were identified.Taking into account cities economic and demographic growth in the modern world, the new reality possesses principally new tasks in the sphere of urban governance and development.There is a gradual revision of the governance of urban development approaches under these conditions. It is increasingly based on advanced technological solutions, digitalization and platformi-zation.